Communication partner training of enrolled nurses working in nursing homes with people with communication disorders caused by stroke or Parkinson's disease. Issue 12 (4th June 2016) - Eriksson, Karin; Forsgren, Emma; Hartelius, Lena; Saldert, Charlotta
Abstract: Purpose : To evaluate the effect of a communication partner training programme directed to enrolled nurses working with people with communication disorders in nursing homes, using an individualised approach. Method : Five dyads consisting of a person with stroke-induced aphasia ( n = 4) or Parkinson's disease (PD) ( n = 1) living in different nursing homes and his/her enrolled nurse participated in the study, which had a replicated single-subject design with multiple baselines across individuals. The main element of the intervention was supervised analysis of video-recorded natural interaction in everyday nursing situations and the formulation of individual goals to change particular communicative strategies. Results : Outcome was measured via blinded assessments of filmed natural interaction obtained at baseline, intervention and follow-up and showed an increased use of the target communicative strategies. Subjective measures of goal attainment by the enrolled nurses were consistent with these results. Measures of perceived functional communication on behalf of the persons with communication disorders were mostly positive; four of five participants with communication disorders and two of five enrolled nurses reported improved functional communication after intervention. Conclusions : The use of an individualised communication partner training programme led to significant changes in natural interaction, which contributes importantly to a growing body of knowledge regarding communication partner training. Implications for rehabilitation: Communication partner training can improve the communicative environment of people with communication disorders. For people with communication disorders who live in institutions, the main conversation partner is likely to be a professional caretaker. An individualised approach for communication partner training that focussed on specific communication patterns was successful in increasing the use of supportive strategies that enrolled nurses used in natural interaction with persons with communication disorders. The training also positively affected the perceived functional communication of the persons with communication disorders.